2022
DOI: 10.1186/s12903-022-02268-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysing root roughness and smear layer relationship by comparing contemporary dental curettes with conventional dental curettes: a randomised controlled trial

Abstract: Background Root debridement procedures for the treatment of periodontal diseases, produces root surface irregularities and smear layer on the root surface that can adversely affect the healing of periodontal tissues. The objective of the present study was to evaluate the surface texture of root after hand instrumentation with Gracey curette, After Five curette, and Mini Five curette. Methods A randomised, controlled clinical trial was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, cumulative evidence suggests that ultrasonic-based devices and manual instrumentation are equally effective in treating periodontal pockets [ 18 ]. Additionally, root surfaces demonstrated rougher surfaces, more gouges, and thicker smear layers when curettes were used as compared to ultrasonic scalers [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cumulative evidence suggests that ultrasonic-based devices and manual instrumentation are equally effective in treating periodontal pockets [ 18 ]. Additionally, root surfaces demonstrated rougher surfaces, more gouges, and thicker smear layers when curettes were used as compared to ultrasonic scalers [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our research, the presence of mesial concavity in the upper first premolar teeth could be a factor in the development of periodontitis. In this instance, treatment should focus on these unique anatomical regions with appropriate instruments, such as Mini Five curettes, whose blades are half the size of After Five or regular Gracey curettes [ 21 ]. A shorter blade allows easier insertion and adaptation in deep, narrow pockets; furcation areas; developmental grooves; line angles; and deep, tight facial, lingual, or palatal pockets [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clean root surfaces have the clinical importance of minimalizing bacterial plaque accumulation, therefore preventing calculus, 3 and easing the reattachment of fibrous tissue of the gingival. 6,22 Some studies on plaque accumulation showed a positive relation between root surface roughness and plaque growth. 23 However, the surface roughness effect of the instruments used is still not clear.…”
Section: Volumementioning
confidence: 99%
“…3,4 Surface qualities are not important for physiological tissue healing but is for regeneration. 5,6 Many clinicians believe that a clean and hard tooth surface is the endpoint of mechanical scaling and root planning (SRP); but this may lead to pulpitis or hypersensitivity after extensive removal of hard tissues. 7 So, it is recommended to remove as little tooth structure as possible to obtain a shapely surface.…”
Section: Introductionmentioning
confidence: 99%